Are more nickel ions released from NiTi wires after sterilisation? - Poosti Maryam; Rad Hossein Pezeshki; Kianoush Kamyar; Hadizadeh Behzad (Sciendo, 2023)
Increased concentrations of nickel ions may be released into saliva from recycled NiTi archwires.